Trial-Based Functional Analysis Informs Treatment for Vocal Scripting. Issue 3 (May 2018) - Rispoli, Mandy; Brodhead, Matthew; Wolfe, Katie; Gregori, Emily
Research on trial-based functional analysis has primarily focused on socially maintained challenging behaviors. However, procedural modifications may be necessary to clarify ambiguous assessment results. The purposes of this study were to evaluate the utility of iterative modifications to trial-based functional analysis on the identification of putative reinforcement and subsequent treatment for vocal scripting. For all participants, modifications to the trial-based functional analysis identified a primary function of automatic reinforcement. The structure of the trial-based format led to identification of social attention as an abolishing operation for vocal scripting. A noncontingent attention treatment was evaluated using withdrawal designs for each participant. This noncontingent attention treatment resulted in near zero levels of vocal scripting for all participants. Implications for research and practice are presented.